PENERAPAN SELF ASSESMENT SYSTEM DANTAX COMPLIANCE WAJIB PAJAK PENGHASILAN DALAM PENCAPAIAN TARGET PENERIMAAN PAJAK PENGHASILAN PADA KPP PRATAMA SEKAYU - Farida Aryani (Universitas Indo Global Mandiri)
This research is an applied research of quantitative descriptive. The use of quantitative descriptive in this research is expected to give a concrete description through the calculation and graphic representation which describe the application of self assessment system and tax compliance of Personal Tax Payer and also target achieving of tax receiving of income tax at KPP Pratama Sekayu from 2011 till 2013. The result of this research shows that: The application of self assessment system by Personal Tax Payer is lower than Institutional Tax Payer, this is approved by the amount of Personal Tax Payer that report and pay not on time and the amount is bigger than the amount of Institutional Tax Payer and the average for three years of Personal Tax Payer is 72.92%, meanwhile The Institutional Tax Payer is only 63.09%. Furthermore, the tax compliance in reporting the tax through the conveying of Annual Notification Letter (SPT) is on time and also the tax payment of either Personal Tax Payer or Institutional Tax Payer is still considered low due to the fact that the percentage average is still under 50%, that is the percentage of tax compliance in reporting the tax, Personal Tax Payer is only 30.56%, on the other hand the Institutional Tax Payer is 47.16%. Then, the percentage average of tax compliance for Institutional Tax Payer the Personal Tax Payer is only 27.08%, on the contrary Tax Payer of Institution is 36.91%. The application of self assessment system and high implementation of tax compliance from Institutional Tax Payer gives contribution to the realization of achieving target of big tax achievement for the average of three years: contribution of Institutional Tax Payer is 99.77%, on the contrary The Personal Tax Payer is only 0.23%. Thus, the contribution of Institutional Tax Payer to the achieving target of income tax achievement is bigger if it is compared with Personal Tax Payer.